2019
DOI: 10.3390/nu11112769
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index Is Associated with Unique Health Conditions and Clinical Outcomes in Chronic Kidney Disease Patients

Abstract: Malnutrition is prevalent in patients with chronic kidney disease (CKD). However, current nutrition screening tools are not specific to the CKD population. In the present study, we aimed to investigate whether the geriatric nutritional risk index (GNRI), a simple tool designed for assessing nutrition-related risks in the elderly population, is associated with unique aspects of CKD such as fluid status, residual renal function, proteinuria, and inflammation, and whether it predicts clinical outcomes. The GNRI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…59À61 However, cutoff points of the GNRI score in elderly patients with ARF can differ from those with chronic diseases because the clinical and demographic characteristics of elderly patients with ARF are different from those with chronic diseases. 30,32,33 Most studies converted the GNRI score into categorical variable based on the distribution of the GNRI, which reduced the statistical credibility. To address this limitation, the RCS method, which has been used in various studies with large sample sizes, was adopted in our study to determine the cutoff point of the GNRI score based on the potential linear or non-linear relationship of the risk for malnutrition assessed by the GNRI score and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59À61 However, cutoff points of the GNRI score in elderly patients with ARF can differ from those with chronic diseases because the clinical and demographic characteristics of elderly patients with ARF are different from those with chronic diseases. 30,32,33 Most studies converted the GNRI score into categorical variable based on the distribution of the GNRI, which reduced the statistical credibility. To address this limitation, the RCS method, which has been used in various studies with large sample sizes, was adopted in our study to determine the cutoff point of the GNRI score based on the potential linear or non-linear relationship of the risk for malnutrition assessed by the GNRI score and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…24 For instance, Lin et al reported cut-off values (69.7À92.4 vs 92.5À98.2 vs 98.3À110.2) in patients with chronic kidney disease and Kanemasa et al reported cut-off values (< 96.8 vs 96.8) in patients with diffuse large B cell lymphoma. 30,33 This indicates the lack of unified cutoff points for the GNRI score among all populations. In view of this, our study aimed to determine the appropriate cutoff points for the GNRI score in elderly patients with ARF.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the abovementioned information, we consider that the low GNRI group would probably have PEW. An association between the GNRI and inflammation has been reported [ 22 , 23 ]. Overall, we suggest that a low GNRI may detect disorders linked to decreased bone strength through PEW in patients undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on all of the three used nutrition assessment tools (SGA, GNRI, and MIS), our patients had normal nutrition status or mild–moderate malnutrition. Only GNRI was related to leptin change largely due to the main constituents of this index, i.e., albumin and body weight, and due to the better performance in detecting sarcopenia [ 21 ]. Furthermore, elevated pre and post-transplant leptin concentration correlated with weaker handgrip strength.…”
Section: Discussionmentioning
confidence: 99%
“…GNRI does not require patient interviewing and therefore it was chosen as an additional nutrition measure. It has been shown to be an appropriate nutrition screening tool and prognostic predictor in the CKD population [ 21 ].…”
Section: Methodsmentioning
confidence: 99%